Hubungan Kesadaran, Pengetahuan dan Pemahaman, dan Kualitas Pelayanan Dengan Kemauan Membayar Pajak Bumi dan Bangunan di Desa Dukuhturi Kecamatan Dukuhturi Kabupaten Tegal - Asih Pamungkas; Sri Murdiati; Okti Rustianti (Faculty of Economics and Business, University of Pancasakti Tegal, 2017)
The purpose of this study is to analyze the relationship of awareness, knowledge and understanding, and the quality of service together with the willingness to pay land and building taxes in Dukuhturi Village, DukuhTuri District, Tegal Regency. Data collection methods used in this study were questionnaires, and literature studies. While the data analysis method used is Spearman rank correlation analysis, Spearman rank correlation test, multiple correlation analysis, significance test multiple correlation coefficient, and coefficient of determination analysis. The results of data analysis using Spearman rank correlation prove that there is a significant relationship of awareness with the willingness to pay taxes in Dukuhturi District, Tegal Regency, with a Spearman rank correlation value of 0.476 and a significance value of 0,000 so the first hypothesis is acceptable. The results of data analysis using Spearman rank correlation prove that there is a significant relationship of knowledge and understanding with the willingness to pay taxes in Dukuhturi District, Tegal Regency, with a Spearman rank correlation value of 0.509 and a significance value of 0,000 so the second hypothesis is acceptable. The results of data analysis using Spearman rank correlation prove that there is a significant relationship of service quality with the willingness to pay taxes in Dukuhturi District of Tegal Regency, with a Spearman rank correlation value of 0.524 and a significance value of 0,000 so the third hypothesis is acceptable. The results of data analysis using multiple correlation prove that there is a significant relationship of awareness, knowledge and understanding, and service quality together with the willingness to pay taxes in Dukuhturi District, Tegal Regency, with a multiple correlation value of 0.665 and a calculated F value of 81.08> Ftable is 2.63 so the fourth hypothesis is acceptable.